KEBERSIHAN ORGAN REPRODUKSI PADA PEREMPUAN PEDESAAN DI KELURAHAN POLAMAN KECAMATAN MIJEN SEMARANG - Eti Rimawati; Agus Perry Kusuma; Sri Sunaryati (VISIKES: Jurnal Kesehatan Masyarakat, 2012)
Background: Women have a susceptibility to transmission of sexually transmitted infections because of anatomical-biological condition of the female reproductive organs causing pelvic structure of women in a position to â€œholdâ€ and the female reproductive organs are â€œentered intoâ€. Cleanliness of the reproductive organs become of vital importance to women in order to avoid reproductive tract infections and cervical cancer. In fact women always put their interests on the final sequence, in which increasingly scarce family resources led to a woman sacrifice their health at the expense of sacrificing time, energy, physical and material to support his family. This is particularly noticeable in rural women are always identified with low education, knowledge and skills. This study aims to describe the behavior of the female reproductive organ hygiene in the rural village of Polaman-Mijen Semarang city.Method: This research is qualitative exploration of research using a case study approach, where data collection is done through in-depth interviews to 10 women in the village. Triangulation of sources used for data validity: peers, parents and health cadres. Furthermore, the data analyzed by thematicResult: Most village women use betel soap to clean their reproductive organs, by the way from back to front, use sanitary napkins during menstruation production from the factory withan average frequency of replacement 2-3 times a day. In the selection of underwear, they have considered the comfortable and absorb perspiration. However, it turns out there are stillcomplaints of vaginal discharge, from which does not disturb until the disturbing comfort. In fact there are some village women who frequently experience vaginal discharge that causediscomfort (itching).Conclusion: The need for increased knowledge about reproductive health for rural women and their mothers, as the people closest to young people through the use of media that is often used by those.Keywords: hygiene, reproductive organ, Woman